PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GROUP TO GROUP TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN 1 LUBUK BASUNG TAHUN PELAJARAN 2013/2014 - Awita, Febri; Rahmi, Rahmi; Cesaria, Anna (Pendidikan Matematika, 2013)
This research is motivated by the students understanding of mathematical concepts is low and less students are responsible for a given task . The research aims to determine whether students understanding of mathematical concepts by applying active learning types Group To Group better than the students understanding of mathematical concepts by applying conventional teaching eighth grade students MTsN 1 Lubuk Basung academic year 2013/2014 . This type of research is experimental research , with a random design on the subject. The research instrument is the final test to learn that contain indicators of understanding the concept .Based on the analysis of data obtained by the average value of the experimental class higher than the control class . Hypothesis testing using t . From the calculations, t = 1.80 is greater than Â = 1,70, the hypothesis is accepted . Based on the hypothesis test results concluded that the students understanding of mathematical concepts that apply active learning types Group To Group better than the students understanding of mathematical concepts by applying conventional learning .